Colloid lead-acid storage battery repair liquid and preparation method thereof
By using potassium nitrate, concentrated sulfuric acid, sodium alginate and xylitol in the lead-acid battery repair solution, combined with the high-density characteristics of deuterium water, the middle and lower layers of active substances inside the battery are activated, which solves the problem that existing repair agents are difficult to activate the active substances in the lower layers of active substances, and achieves a more stable repair effect and a longer battery life.
Patent Information
- Application Number
- CN202411501088.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-28
AI Technical Summary
Existing lead-acid battery repair agents or repair fluids are difficult to effectively activate the active substances in the lower layer of the battery, resulting in unstable repair effect, which can easily cause corrosion and deposition problems, affecting battery life.
Using a repair solution including potassium nitrate, concentrated sulfuric acid, sodium alginate and xylitol, it quickly penetrates into the battery through the high-density characteristics of deuterium water, activates the middle and lower active substances, and improves the stability and solubility of the repair solution through potassium nitrate and sodium alginate.
The comprehensive activation and repair of the active substances in the upper, middle and lower layers of colloidal lead-acid battery is achieved, the lead sulfate layer on the surface of the electrode plate is removed, the battery life is extended, the electrolyte layering and corrosion phenomenon is reduced, and the battery reliability and stability is improved.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead-acid battery repair and maintenance, and in particular relates to a colloidal lead-acid battery repair liquid and a preparation method thereof. Background Art
[0002] Colloidal lead-acid batteries are lead-acid batteries that use silicate gel as electrolyte. They are also called colloidal batteries, silica gel batteries or colloidal batteries. The electrolyte uses silicate gel instead of the liquid electrolyte of conventional lead-acid batteries. This silicate gel is a semi-solid electrolyte. Due to its low cost, easy maintenance, and stable performance, it is widely used in electric vehicles, energy storage systems, backup power supplies and other fields. As the use time of colloidal lead-acid batteries increases, colloidal lead-acid batteries will have problems such as decreased capacity, increased internal resistance, and decreased charging and discharging efficiency, which seriously affects its efficiency and life. At present, hydrotherapy repair, high-current charging repair, high-frequency pulse repair, and chemical activator repair have been used to repair lead-acid batteries. However, these repair methods can only solve part of the sulfation problem. It is very easy to cause capacity reduction and rapid failure due to the introduction of new impurities. At the same time, there is also the possibility of reduced quality of active substances inside the battery, resulting in unstable repair effects and even secondary damage to the battery.
[0003] There are studies on the problems existing in the current repair methods of lead-acid batteries in the prior art, such as patent application CN109473732A-a repair agent for lead-acid batteries and a repair method for lead-acid batteries, which uses a repair agent of sodium sulfate, ammonium sulfate, manganese dioxide, sodium hypophosphite, trifluoroacetic acid, ammonium phosphate and pyrogallol, which can remove partially crystallized lead sulfate inside the battery, while maintaining the active substances and internal structure of the battery, and extending the service life of the repaired lead-acid battery. Another example is patent application CN115714209A-a lead-acid battery repair liquid and its preparation method and application, which uses nanographene stock solution-acid solution as the main component system. A protective film is formed on the battery plate to reduce the internal resistance of the battery, reduce the crystallinity of lead sulfate and improve the low-temperature performance of the battery. The lead-acid battery repair agent or repair liquid mentioned above solves the problems of limited repair effect, introduction of new impurities, and secondary damage to battery performance in the current lead-acid battery repair method. However, the existing lead-acid battery repair agent or repair liquid can only activate and repair the active materials in the middle and upper layers of the battery, but it is difficult to effectively activate and repair the active materials in the middle and lower layers of the battery, so that the improvement effect on the internal structure of the lead-acid battery is limited, which can easily cause corrosion and deposition problems inside the lead-acid battery, thereby seriously affecting the repair effect of the lead-acid battery. To this end, a new technical solution is needed to solve the above technical problems. Summary of the invention
[0004] The purpose of the present invention is to provide a colloidal lead-acid battery repair liquid and a preparation method thereof, so as to solve the problem raised in the above-mentioned background technology that the current lead-acid battery repair agent or repair liquid is difficult to effectively activate the active substances in the lower layer inside the repair battery, so that the improvement effect on the internal structure of the lead-acid battery is limited, and it is very easy to cause corrosion and deposition problems inside the lead-acid battery, thereby seriously affecting the repair effect of the lead-acid battery.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a colloidal lead-acid battery repair liquid, characterized in that it comprises the following components in weight percentage: 0.03-0.07% of potassium nitrate of premium pure product, 30-33% of concentrated sulfuric acid of 98% purity industrial grade product, 0.6-0.9% of sodium alginate powder of purity ≧99%, 0.5-0.9% of xylitol powder of purity ≧99%, 8-10% of deuterated water of industrial grade product, and 57-60% of pure water with conductivity ≤2us / cm.
[0006] Further, the specific steps of preparing the colloidal lead-acid battery repair solution according to the above repair solution raw material formula are as follows: S1. Mix and stir the formulated amounts of potassium nitrate, xylitol, sodium alginate, deuterated water and 10% of the formulated amount of pure water to obtain a mixed liquid; S2, pour the formula amount of concentrated sulfuric acid into 80% of the formula amount of pure water, slowly stir and cool the temperature to 30-40°C to obtain dilute acid; S3, pour the mixed liquid prepared in S1 into the diluted acid prepared in S2 and stir for 20 to 40 minutes to obtain the initial repair liquid; S4. After the initial product of the repair liquid is cooled to 15-25°C, its density is tested. If the density is unqualified, the initial product of the repair liquid needs to be poured into pure water with a formula volume of 10% to adjust the density. After the density is qualified, a finished product of the repair liquid with a density of 1.23-1.27 g / mL at room temperature is obtained.
[0007] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention utilizes the high density of deuterium water, which can not only effectively activate and repair the active substances in the middle and upper layers of the colloidal lead-acid battery, but also quickly penetrate into the inner bottom of the colloidal lead-acid battery, activate and repair the active substances in the middle and lower layers that are difficult to reach with the existing repair agent or repair liquid, remove the lead sulfate layer on the surface of the plate, thereby achieving the purpose of fully repairing the colloidal lead-acid battery, greatly improving the internal structure of the colloidal lead-acid battery, and helping to extend the service life of the battery. At the same time, it also effectively reduces the stratification of the electrolyte, promotes the circulation of ions inside the colloidal lead-acid battery, and adds potassium nitrate to the repair liquid. Raw materials, so that the lead sulfate layer attached to the surface of the plate is gradually dissolved in the repair liquid, which effectively improves the solubility of sulfate. By adding sodium alginate and xylitol raw materials to the repair liquid, the stability of the repair liquid is effectively improved, the balance inside the colloidal lead-acid battery is maintained, and a protective layer can be formed inside the colloidal lead-acid battery, which effectively reduces the corrosion phenomenon inside the battery, and also reduces the deposition of harmful substances such as lead sulfate, thereby effectively alleviating the deterioration of the internal structure of the colloidal lead-acid battery, improving the reliability and stability of the colloidal lead-acid battery, and ensuring the repair effect of the colloidal lead-acid battery; 2. The present invention adopts environmentally friendly materials as raw material components of the repair liquid, making the preparation of the repair liquid safer and more environmentally friendly, effectively avoiding the pollution of harmful substances to the colloidal lead-acid battery and the environment. Through strict stirring and temperature control, it not only improves the repair effect, but also reduces the risk of battery performance degradation and secondary damage caused by the introduction of impurities. At the same time, it also ensures the uniformity and stability of the repair liquid components, thereby ensuring the reliability and consistency of the repair effect; 3. The present invention adopts pure water to adjust the density of the initial repair liquid, so that the repair liquid can be flexibly adjusted according to actual needs to adapt to the repair needs of the colloidal lead-acid battery under different conditions, thereby improving the pertinence and effectiveness of the repair. The preparation method of stirring and density adjustment makes the preparation process of the repair liquid simpler, easier to operate and controllable, so that the problems of the colloidal lead-acid battery such as decreased capacity, increased internal resistance, and reduced charging and discharging efficiency under the activation and repair of the repair liquid are significantly improved, and the overall performance of the colloidal lead-acid battery is significantly improved, thereby effectively extending the life and use time of the repaired colloidal lead-acid battery, having good economic benefits and meeting the requirements of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 It is a curve chart of the discharge time of the cyclic test of Example 1, Example 2, Example 3 and the comparative example of the present invention. DETAILED DESCRIPTION
[0009] The following examples are used to further illustrate the content of the present invention, but do not limit the application of the present invention. Embodiment 1:
[0010] The present embodiment provides a colloidal lead-acid battery repair liquid, and the preparation method thereof comprises the following steps: firstly, 0.069% of potassium nitrate of a high-grade pure product, 0.52% of xylitol powder with a purity of ≥99%, 0.88% of sodium alginate powder with a purity of ≥99%, 9.04% of deuterium water of an industrial-grade product and 10% of pure water of 59.351% are mixed and stirred to obtain a mixed liquid; secondly, 30.14% of concentrated sulfuric acid of an industrial-grade product with a purity of 98% is poured into 59. The mixture is slowly stirred in 80% pure water in 351% and the temperature is cooled to 30-40°C to obtain dilute acid; then the mixed liquid and the dilute acid are stirred for 20-40 minutes to obtain a preliminary repair liquid; after the preliminary repair liquid is cooled to 15-25°C, its density is tested. If the density is unqualified, the preliminary repair liquid is poured into the remaining 10% pure water in 59.351% to adjust the density until the measured density is 1.23-1.27 g / mL at room temperature to obtain a finished repair liquid.
[0011] Among them, since deuterium water is an isotope of hydrogen, the density of deuterium water under standard conditions is 1.105g / mL, which is heavier than common water. During the discharge process, the colloidal lead-acid battery will continuously consume sulfuric acid in the electrolyte, and sulfuric acid begins to be consumed from top to bottom. When the electrolyte concentration is too low, it will not be able to support the internal chemical reaction of the battery, that is, the battery discharge is terminated. At present, the density of the electrolyte of the maintenance-free lead-acid battery on the market after full discharge is 1.08-1.13g / mL. It can be seen that the density of pure deuterium water is heavier than the electrolyte after full discharge. Therefore, when the electrolyte density is lower than 1.105g / mL during the battery discharge process, deuterium water begins to sink continuously, balancing the electrolyte concentration of the upper, middle and lower layers inside the battery. At the same time, deuterium water also has low viscosity and high activity, and the water molecule clusters are small, and the resistance received in the AGM separator paper is smaller, which can improve the ability of the electrolyte to transport oxygen; Potassium nitrate is different from sulfate added to other repair solutions on the market. Potassium nitrate is a strong electrolyte. It can gradually dissolve the lead sulfate layer attached to the surface of the plate in the electrolyte, which can effectively increase the dissolution of sulfate. Concentrated sulfuric acid is a key substance in the electrochemical reaction of colloidal lead-acid batteries and helps to remove lead sulfate deposits on the surface; sodium alginate can effectively improve the stability of the repair fluid and maintain the internal balance of the colloidal lead-acid battery; xylitol can reduce oxygen evolution, inhibit the formation of lead sulfate, and improve the utilization rate of active substances; pure water is the main solvent and is used to dilute and adjust the concentration of the repair fluid.
[0012] The finished repair liquid prepared in this embodiment was injected into a group of 48V20Ah batteries on the market that had been used for 12 months, and the group of batteries was discharged to a single cell voltage of 1.75-1.8V, and the finished repair liquid prepared in this embodiment was injected into the single cell until it just covered the separator paper, and the battery repair instrument was connected for repair. After the repair, the four batteries were cycled according to the method described in 5.12 of GB / T 22199.1-2017 until the end of their life. The test results are shown in the following comparison table. Embodiment 2:
[0013] The preparation process of the colloidal lead-acid battery repair liquid of this embodiment is consistent with that of Example 1, except for the different formula amounts, namely: the weight percentage of potassium nitrate of the superior pure product is 0.052%, the weight percentage of xylitol powder with a purity ≧99% is 0.70%, the weight percentage of sodium alginate powder with a purity ≧99% is 0.72%, the weight percentage of deuterium water of the industrial-grade product is 9.95%, the weight percentage of pure water is 57.008%, and the weight percentage of concentrated sulfuric acid of the industrial-grade product with a purity of 98% is 31.57%.
[0014] The finished repair liquid prepared in this embodiment was injected into a group of 48V20Ah batteries on the market that had been used for 12 months, and the group of batteries was discharged to a single cell voltage of 1.75-1.8V, and the finished repair liquid prepared in this embodiment was injected into the single cell until it just covered the separator paper, and the battery repair instrument was connected for repair. After the repair, the four batteries were cycled according to the method described in 5.12 of GB / T 22199.1-2017 until the end of their life. The test results are shown in the following comparison table. Embodiment 3:
[0015] The preparation process of the colloidal lead-acid battery repair liquid of this embodiment is consistent with that of Example 1, except for the different formula amounts, namely: the weight percentage of potassium nitrate of the superior pure product is 0.034%, the weight percentage of xylitol powder with a purity ≧99% is 0.87%, the weight percentage of sodium alginate powder with a purity ≧99% is 0.61%, the weight percentage of deuterium water of the industrial-grade product is 8.03%, the weight percentage of pure water is 57.566%, and the weight percentage of concentrated sulfuric acid of the industrial-grade product with a purity of 98% is 32.89%.
[0016] The finished repair liquid prepared in this embodiment was injected into a group of 48V20Ah batteries on the market that had been used for 12 months, and the group of batteries was discharged to a single cell voltage of 1.75-1.8V, and the finished repair liquid prepared in this embodiment was injected into the single cell until it just covered the separator paper, and the battery repair instrument was connected for repair. After the repair, the four batteries were cycled according to the method described in 5.12 of GB / T 22199.1-2017 until the end of their life. The test results are shown in the following comparison table.
[0017] Comparative Example: A group of 48V20Ah finished products without the repair fluid prepared by the present invention that have been used for 12 months on the market were selected, and four batteries were subjected to cycle testing according to the method described in 5.12 of GB / T 22199.1-2017 until the end of their life. The test results are shown in the following comparison table.
[0018] The following is a comparison table of battery cycle test data of Examples 1-3 and Comparative Example: ; As can be seen from the above table, the repair solution prepared by mixing potassium nitrate, sodium alginate, xylitol and deuterated water with pure water and concentrated sulfuric acid has fewer added ingredients, simpler preparation process, and can quickly reach the bottom of the battery compared to the existing repair solution. During the repair process, it can activate and repair the active substances in the upper, middle and lower layers of the colloidal lead-acid battery, remove the lead sulfate layer on the surface of the plate, thereby achieving the purpose of fully repairing the colloidal lead-acid battery, greatly improving the internal structure of the colloidal lead-acid battery, and helping to extend the service life of the battery. At the same time, it also effectively reduces the stratification of the electrolyte, promotes the circulation of ions inside the colloidal lead-acid battery, reduces the corrosion phenomenon inside the battery, reduces the deposition of harmful substances such as lead sulfate, alleviates the deterioration of the internal structure of the colloidal lead-acid battery, improves the reliability and stability of the colloidal lead-acid battery, and ensures the repair effect of the colloidal lead-acid battery.
Claims
1. A colloidal lead-acid battery repairing liquid, characterized in that: The invention comprises the following components in percentage by weight: 0.03-0.07% potassium nitrate, 30-33% concentrated sulfuric acid, 0.6-0.9% sodium alginate, 0.5-0.9% xylitol, 8-10% deuterated water and 57-60% pure water.
2. A colloidal lead-acid battery repairing liquid according to claim 1, characterized in that: The potassium nitrate is a high-grade pure product, the concentrated sulfuric acid is an industrial-grade product with a purity of 98%, and the deuterium water is an industrial-grade product.
3. A colloidal lead-acid battery repairing solution according to claim 1, characterized in that: The sodium alginate and xylitol are both powders with a purity of ≥99%.
4. A colloidal lead-acid battery repairing solution according to claim 1, characterized in that: The conductivity of the pure water is ≤2us / cm.
5. A method for preparing a colloidal lead-acid battery repair solution as described in any one of claims 1 to 4, characterized in that: The specific steps are as follows: S1. Mix and stir the formulated amounts of potassium nitrate, xylitol, sodium alginate, deuterated water and 10% of the formulated amount of pure water to obtain a mixed liquid; S2, pour the formula amount of concentrated sulfuric acid into 80% of the formula amount of pure water and slowly stir to obtain dilute acid; S3, pouring the mixed liquid prepared in S1 into the diluted acid prepared in S2, stirring and mixing to obtain a preliminary repair liquid; S4. After the initial repairing liquid is cooled, its density is tested, and when the density is qualified, the finished repairing liquid is obtained.
6. The method for preparing a colloidal lead-acid battery repairing solution according to claim 5, characterized in that: In S2, the temperature needs to be cooled to 30-40°C during the stirring process.
7. The method for preparing a colloidal lead-acid battery repairing solution according to claim 5, characterized in that: In S3, the stirring and mixing time is 20 to 40 minutes.
8. The method for preparing a colloidal lead-acid battery repairing solution according to claim 5, characterized in that: In S4, the cooling temperature is 15 to 25°C.
9. The method for preparing a colloidal lead-acid battery repairing solution according to claim 5, characterized in that: In S4, if the density is not up to standard, the initial repair liquid needs to be poured into pure water with a volume of 10% of the formula to adjust the density.
10. The method for preparing a colloidal lead-acid battery repairing solution according to claim 5, characterized in that: In S4, the density of the finished repair liquid at room temperature is 1.23-1.27 g / mL.
Citation Information
Patent Citations
Recovery agent of lead-acid storage battery and recovery method of lead-acid storage battery
CN109473732A